2019
DOI: 10.1007/s13524-019-00827-w
|View full text |Cite
|
Sign up to set email alerts
|

Educational Variations in Cohort Trends in the Black-White Earnings Gap Among Men: Evidence From Administrative Earnings Data

Abstract: Despite efforts to improve the labor market situation of African Americans, the racial earnings gap has endured in the United States. Most prior studies on racial inequality have considered its cross-sectional or period patterns. This study adopts a demographic perspective to examine the evolution of earnings trajectories among white and black men across cohorts in the United States. Using more than 40 years of longitudinal earnings records from the U.S. Social Security Administration matched to the Survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 84 publications
(120 reference statements)
1
35
0
Order By: Relevance
“…In this scenario, therefore, ethnic inequality in earnings increases over the life course both between and within educational levels, thus contributing to overall increase in ethnic earnings inequality over the life course. This scenario explains part of the rise in earnings inequality between white and African American men in the United States (Cheng et al 2017).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In this scenario, therefore, ethnic inequality in earnings increases over the life course both between and within educational levels, thus contributing to overall increase in ethnic earnings inequality over the life course. This scenario explains part of the rise in earnings inequality between white and African American men in the United States (Cheng et al 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Among men with low education, by contrast, race and ethnicity have a smaller impact on career earnings growth, mainly in their early career years (Tomaskovic-Devey et al 2005). Cheng et al (2017) recently showed that race continues to be a salient dimension of economic inequality over the life course, particularly at the top and the bottom of the educational distribution, whereas among workers with only a high school degree, the racial gap is declining. Contrary to that, Sakamoto, Tamborini, and Kim (2018) found that the negative net effect for African American men on long-term earnings is more severe at lower levels of education and is explained by unstable employment history among this racial group.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…A large literature illustrates how existing patterns of social stratification shape socio-economic outcomes and the effects of large events and crises. Dudel and Myrskylä (2017); Cheng et al (2019) and Killewald and Zhuo (2019) illustrate disparities in occupational wage gaps and other labor market outcomes on the basis of age, gender, and ethnicity both in the US and abroad. Dudel and Myrskylä (2017) show that the Great Recession shortened the life expectancy for senior workers specially among white men.…”
Section: Related Researchmentioning
confidence: 99%